Effectiveness of labels in digital art experience: psychophysiological and behavioral evidence - Castellotti, Serena; D’Agostino, Ottavia; Del Viva, Maria Michela (Frontiers in Psychology, 2024)
Nowadays museums make large use of digital materials (e.g., virtual tours) to attract visitors. Therefore, it is worthwhile investigating which variables affect the engagement with art outside the museum, and whether digital reproductions of artworks are as effective as museum originals in producing a satisfying aesthetic experience.Here we tested the effectiveness of introducing additional informative materials on the artistic enjoyment of contemporary paintings presented on a computer screen. Naïve observers were exposed to essential and descriptive labels before viewing artworks. We flanked traditional measurement methods -viewing times and questionnaires, with biometric parameters -pupil responses, eye movements, heart rate, and electrodermal activity. The results were then compared to our previous museum study that adopted the same experimental paradigm.Our behavioral and psychophysiological data lead to a complex pattern of results. As found in the museum setting, providing detailed descriptions decreases complexity, evokes more positive sensations, and induces pupil dilation but does not enhance aesthetic appreciation. These results suggested that informative labels improve understanding and emotions but have a limited impact on the hedonic evaluation of artworks in both contexts. However, other results do not mirror those found in the museum; in the laboratory setting, participants spend a similar amount of time, have a comparable gaze behavior, and their electrodermal activity and heart rate do not change when viewing artworks with different types of labels. The main difference between the lab and museum settings is the shorter time spent viewing digital reproductions vs. real paintings, although subjective ratings (e.g., liking, interest) are comparable.Overall, this study indicates that the environmental context does impact the aesthetic experience; although, some beneficial effects of introducing additional relevant content in labels accompanying artworks can also be acquainted through digital media outside of the museum.